Validation Analysis of a Geriatric Dehydration Screening Tool in Community-Dwelling and Institutionalized Elderly People - Rodrigues, S. (2015)
Dehydration is common among elderly people. The aim of this study was to perform validation analysis of a geriatric dehydration-screening tool (DST) in the assessment of hydration status in elderly people. This tool was based on the DST proposed by Vivanti et al., which is composed by 11 items (four physical signs of dehydration and seven questions about thirst sensation, pain and mobility), with four questions extra about drinking habits. The resulting questionnaire was evaluated in a convenience sample comprising institutionalized (n = 29) and community-dwelling (n = 74) elderly people. Urinary parameters were assessed (24-h urine osmolality and volume) and free water reserve (FWR) was calculated. Exploratory factor analysis was used to evaluate the scale's dimensionality and Cronbach's alpha was used to measure the reliability of each subscale. Construct's validity was tested using linear regression to estimate the association between scores in each dimension and urinary parameters. Two factors emerged from factor analysis, which were named "Hydration Score" and "Pain Score", and both subscales showed acceptable reliabilities. The "Hydration Score" was negatively associated with 24-h urine osmolality in community-dwelling; and the "Pain Score" was negatively associated with 24-h urine osmolality, and positively associated with 24-h urine volume and FWR in institutionalized elderly people.